FRIENDLY (FMT) is an RNA binding protein associated with cytosolic ribosomes at the mitochondrial surface. (12th September 2022) - Hemono, Mickaele; Salinas‐Giegé, Thalia; Roignant, Jeanne; Vingadassalon, Audrey; Hammann, Philippe; Ubrig, Elodie; Ngondo, Patryk; Duchêne, Anne‐Marie
SUMMARY: The spatial organization of protein synthesis in the eukaryotic cell is essential for maintaining the integrity of the proteome and the functioning of the cell. Translation on free polysomes or on ribosomes associated with the endoplasmic reticulum has been studied for a long time. More recent data have revealed selective translation of mRNAs in other compartments, in particular at the surface of mitochondria. Although these processes have been described in many organisms, particularky in plants, the mRNA targeting and localized translation mechanisms remain poorly understood. Here, the Arabidopsis thaliana Friendly (FMT) protein is shown to be a cytosolic RNA binding protein that associates with cytosolic ribosomes at the surface of mitochondria. FMT knockout delays seedling development and causes mitochondrial clustering. The mutation also disrupts the mitochondrial proteome, as well as the localization of nuclear transcripts encoding mitochondrial proteins at the surface of mitochondria. These data indicate that FMT participates in the localization of mRNAs and their translation at the surface of mitochondria. Significance Statement: Intracellular trafficking of mRNAs and localized protein synthesis are fundamental mechanisms with respect to protein localization. Recent data have revealed selective translation of mRNAs at the surface of mitochondria. Indeed, one‐third of mRNAs coding for nuclear‐encoded mitochondrial proteins were found at the surface of plant mitochondria. FMT is a plant RNA‐binding protein that participates in the localization of mRNAs and their translation at the surface of mitochondria.